Efektivitas Impression Management Anies Baswedan sebagai Capres 2024 terhadap Sikap Pemilih Pemula - Hayati, Sagita Rahma; Fitriani, Dinda Rakhma (Jurnal Media dan Komunikasi Indonesia, 2025)
This study aims to identify the Impression Management strategies employed by Anies Baswedan through his Instagram account, @aniesbaswedan, during the 2024 presidential campaign, focusing on first-time voters aged 17-21. Impression Management is the process by which an individual intentionally shapes the perception others have of them. Indonesian political figures, including the 2024 presidential candidate, Anies Baswedan, also engage in Impression Management. The research method used is quantitative with a positivism paradigm, involving the distribution of questionnaires to Anies Baswedan's Instagram followers. This study applies Jones & Pittman's (1982) Impression Management theory, encompassing, ingratiation, self-promotion exemplification, intimidation, and supplication, as well as attitude indicators consisting of cognitive, affective, and conative components. The results indicate that the most frequently used strategy by Anies Baswedan is ingratiation, aiming to create the impression of a likeable presidential candidate. The sub-indicators of this strategy are dominated by expressions of sympathy towards others, such as congratulations, condolences, and other sympathetic actions.